Effect and Molecular Mechanisms of Traditional Chinese Medicine on Regulating Tumor Immunosuppressive Microenvironment. (16th June 2015) - Guo, Qiujun; Li, Jie; Lin, Hongsheng
Abstract : Traditional Chinese medicine (TCM) is an important complementary strategy for treating cancer in China. The mechanism is related to regulating the internal environment and remodeling the tumor immunosuppressive microenvironment (TIM). Herein we illustrate how TIM is reformed and its protumor activity on promoting tumor cell proliferation, angiogenesis and lymphangiogenesis, tumor invasion, and the oncogenicity of cancer stem cells. Furthermore we summarize the effects and mechanism of TCM on regulating TIM via enhancing antitumor immune responses (e.g., regulating the expression of MHC molecules and Fas/FasL, attenuating cancerigenic ability of cancer stem cells) and remolding immunosuppressive cells (e.g., reversing immune phenotypes of T lymphocytes and tumor associated macrophages, promoting dendritic cells mature, restraining myeloid derived suppressor cells function, and regulating Th1/Th2 factors). We also reveal the bidirectional and multitargeting functions of TCM on regulating TIM. Hopefully, it provides new theoretical basis for TCM clinical practice in cancer treatment and prevention.